Non-Diffractive Wavefront-Shaping Intraocular Lens with Extended Depth of Focus: First Implantation Experience - K. B. Pershin; N. F. Pashinova; A. Yu. Tsygankov; E. A. Antonov; I. V. Kosova; E. A. Korneeva (Oftalʹmologiâ)
Purpose. Analysis of short-term clinical and functional results of implantation of a new non-diffractive IOL with expanded depth of focus.Patients and methods. The study included 27 patients (35 eyes) after bilateral (8 patients) or monolateral (19 patients) AcrySof IQ Vivity IOL implantation (Alcon, USA) with mean follow-up of 3.8 ± 0.3 (3–5) months. In all cases, IOL implantation was preceded by cataract phacoemulsification or refractive lensectomy. Women accounted for 63 % (n = 17) and men for 37 % (n = 10). AcrySof IQ Vivity DFT015 IOLs were implanted in 24 eyes and toric AcrySof IQ Vivity DFT315, DFT415 and DFT515 IOLs in 11 eyes with clinically significant (more than 1.0 D) astigmatism.Results. There was a significant (p < 0.05) increase in distance and intermediate uncorrected and best corrected visual acuity starting from the 1st day after surgery. An increase from 0.31 ± 0.09 to 0.58 ± 0.12 at the 1st day after the operation, and further up to 0.63 ± 0.13 at the follow-up period of 3 months (p < 0.05) was also registered while assessing near uncorrected visual acuity. In spite of some increase of best corrected near visual acuity in the follow-up period of 3 months in comparison with preoperative period (0.68 ± 0.19 and 0.57 ± 0.16, respectively), these differences were not statisticallysignificant (p > 0.05). After IOL implantation, the spherical refractive index was shown to decrease from –2.75 ± 1.4 in the preoperative period to –0.10 ± 0.73 in the follow-up period of 3 months. Permanent or periodic optical phenomena were detected in 4 patients out of 27 (14.8 %), of them 2 patients (7.4 %) had glare and 2 (7.4 %) — halo. Patients did not complain of difficulties in driving in the dark. In 11 oof 27 cases (40.7 %), patients required spectacle correction for reading. In spite of the need for spectacle correction for near vision in 40 % cases, the vast majority of patients (n = 24; 88.9 %) rated the result of surgery as “excellent” and three (11.1 %) as good.Conclusion. This work presents the first experience in Russia of implantation of a new non-diffractive intraocular lens with an expanded depth of focus forming a wavefront in 35 eyes. The presented data testify to the high efficacy of this IOL for medium distance and far distance vision correction and to the possibility of providing functional near vision. Implantation of the investigated IOL was associated with a low incidence of adverse optical phenomena, such as halo, glare, and discomfort when driving in the dark. The use of this IOL in clinical practice may be an option to achieve the desired outcome in cataract surgery.